2021
DOI: 10.3389/fnins.2021.726505
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Acupuncture on Emotional Disorders in Patients With Menstrual Migraine Without Aura: A Resting-State fMRI Study

Abstract: Background: Menstrual migraine without aura (MMoA) refers to a specific type of migraine that is associated with the female ovarian cycle. It is particularly serious and has brought huge life pressure and mental burden to female patients. Acupuncture has been commonly used to prevent migraines and relieve concomitant emotional disorders; however, the physiological mechanism underlying this intervention remains unclear. This study aimed to use resting-state functional magnetic resonance imaging (rsfMRI) to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…One study found that chronic pain caused a decrease in the gray matter volume of the occipital cortex. Our previous studies of migraine (Zhang et al, 2021) found that the ReHo value of the left middle occipital gyrus or right middle occipital gyrus decreased after acupuncture treatment and that it may be related to the relief of photophobia and the reduction of pain-associated symptoms in migraine patients. These results suggest the occipital lobe's importance to the field of pain and help explain the occipital lobe's higher dFCD variability in CNP.…”
Section: Discussionmentioning
confidence: 91%
“…One study found that chronic pain caused a decrease in the gray matter volume of the occipital cortex. Our previous studies of migraine (Zhang et al, 2021) found that the ReHo value of the left middle occipital gyrus or right middle occipital gyrus decreased after acupuncture treatment and that it may be related to the relief of photophobia and the reduction of pain-associated symptoms in migraine patients. These results suggest the occipital lobe's importance to the field of pain and help explain the occipital lobe's higher dFCD variability in CNP.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the STG belongs to the ventral stream of the visual pathway, effectuated as a link between auditory and visual processing, perception, and memory ( Kravitz et al, 2013 ). A recent study found diminished ReHo value in right STG after acupuncture treatment, indicating emotional disorders in menstrual migraine without aura patients and the association with the acupuncture effects as well ( Zhang et al, 2021 ). However, contrary results of an elevated ReHo value in STG and lowered in MTG were reported after acupuncture in a previous study ( Zhao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both the SDS and SAS comprise 20 items, each of which is scored on a scale of 1–4, ranging from the absence of the symptom (score of 1) to maximal symptoms (score of 4), and a higher score indicates greater severity of depression or anxiety. Standard scores of 53 (equal to the original raw score of 41) for the SAS and 50 (equal to the original raw score of 40) for the SDS were used as the cut-off scores for Chinese clinical significance, where the higher the score, the more severe the depressive or anxious mood ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%